Analisis Implementasi Pelayanan Penerima Bantuan Iuran (PBI) di Puskesmas Bromo Kecamatan Medan Denai - Anjlya Agustin; Erika Desriyani; Mira Indah Pratiwi Limbong; Nisa Azizah Rahma Ginting; Sheila Iga Sirai; Tessya Chaniago; Dewi Agustina (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
BPJS is a public legal entity that is specifically assigned by the government to administer health care insurance for all Indonesian people, especially for the poor so that with the existence of BPJS for health, it is hoped that it can increase equity for all levels of society to access health services easily and not just prioritizing only those who are financially able. The high and low quality of public health is closely related to several supporting factors which include environmental factors, community behavior, and the level of health services which are interrelated between one problem and another. The purpose of this study was to see how the Bromo Health Center, Medan Denai District, implements services for recipients of contribution assistance (PBI) and what are the obstacles to implementing contribution assistance recipients (PBI). The research method that will be used in this study is an observational research method with a cross sectional approach which will be carried out in Medan City in 2022. From interviews with interviewees and BPJS participants it is clear that health services for BPJS PBI users at the Bromo Health Center, Kec. Medan Denai based on Presidential Regulation Number 62 of 2020 concerning Health Insurance Amendments to Presidential Regulation Number 82 of 2018 concerning Health Insurance have not run optimally. Keywords: SJSN, Puskesmas, BPJS